Survival, rooting and biomass of acerola mini-cuttings using purple nutsedge extract - Medeiros Câmara, Francisco Mickael; Soares de Carvalho, Adriano; Mendonça, Vander; da Cruz Paulino, Renan; Porto Diógenes, Francisco Ésio (Comunicata Scientiae, 2016)
With the need of a large-scale seedling production, the application of purple nutsedge extract may represent a promising alternative, contributing to the fruit species propagation. The aim of this study was to evaluate the effects of nutsedge extract on the survival rate, rooting and biomass of acerola’s mini-cuttings. The experimental design was a completely randomized block, with a 5x2 factorial arrangement (five aqueous purple nutsedge extracts of nutsedge (0%, 25%, 50%, 75% and 100%) and two types of mini-cuttings, a pair of entire leaves and a pair of half leaves) resulting in 10 treatments with 5 repetitions and 8 mini-cuttings per repetition. The evaluations were performed at 75 days after planting, when destructive analysis were carried out for morphological characteristics. The evaluates variables were mini-cuttings survival percentage, percentage of mini-cuttings with sprouts, percentage of mini-cuttings with callus, percentage of minicuttings with roots, root system length, shoot dry mass, root dry mass, total dry biomass and the ratio between shoot and root dry mass. For the experiment conditions, the nutsedge extract positively influenced the survival percentage and percentage of sprouting of acerola’s mini-cuttings, however the extract application did not influence the mini-cuttings biomass of, being the results observed with or without the cut on mini-cuttings leaves.